MONETIZATION OF LANDSCAPE-RECREATIONAL AND ETHNO-ECONOMIC POTENTIAL OF MOUNTAIN TERRITORIES OF DAGESTAN AND ALTAI: METHODOLOGICAL ASPECTS OF THE RESEARCH - Magomedhanov, Magomedhan Magomedovic; Sadovoj, Aleksandr Nikolaevic; Magdilov, Mazid Magdievic (History, Archeology and Ethnography of the Caucasus, 2024)
This article aims to define methodological approaches and algorithms for examining contemporary ethnosocial processes associated with the monetization of landscape-recreational and ethno-economic potential in a historical context, using the mountainous territories of Dagestan and Altai as case studies. The relevance of this research stems from the need to optimize social technologies for ensuring national, environmental, and supply security in the transboundary areas of southern Russia, as approved by the Russian state. The study focuses on the “rational component” of state policies implemented in the Caucasus and Sayan-Altai regions during the 20th and early 21st centuries. The authors conducted territorial studies of several taxa within which the interaction and interdependence of demographic, socio-economic, and ethno-cultural processes are most evident. The multidisciplinary approach to the problem (encompassing history, ethnography, geography, and economics) is necessitated by the inherent nature of mountainous areas, characterized by specific natural-climatic, economic-cultural, socio-structural, and demographic features at regional, subregional, interethnic, and ethnic levels. The findings from this study of the Caucasus and Sayan-Altai regions have the potential to form a basis for scientific forecasting of major trends in evolving ethno-social situations.